A Functional Role of Fibroblast Growth Factor Receptor 1 (FGFR1) in the Suppression of Influenza A Virus Replication - Liu, Xin (PLoS One, 2015)
Influenza A virus causes annual epidemics and occasional pandemics in humans. Here, we investigated four members of the fibroblast growth factor receptor (FGFR) family; FGFR1 to 4, and examined their expression patterns in human lung epithelial cells A549 with influenza A virus infection. We identified a functional role of FGFR1 in influenza A/Puerto Rico/8/1934 (PR8) and A/Anhui/01/2005 (H5N1) virus replication. Our results showed that FGFR1 silencing by siRNA interference promoted influenza A/PR8 and H5N1 virus replication in A549 cells, while lentivirus-mediated exogenous FGFR1 expression significantly suppressed influenza A virus replication; however, FGFR4 did not have the same effects. Moreover, FGFR1 phosphorylation levels were downregulated in A549 cells by influenza A virus infection, while the repression of FGFR1 kinase using PD173074, a potent and selective FGFR1 inhibitor, could enhance virus replication. Furthermore, we found that FGFR1 inhibits influenza virus internalization, but not binding, during viral entry. These results suggested that FGFR1 specifically antagonizes influenza A virus replication, probably by blocking viral entry.